PENGGUNAAN MODEL PEMBELAJARAN INKUIRI PADA MATERI MACAM-MACAM GAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV DI SD NEGERI OEBOLE KABUPATEN ROTE NDAO - Vivi Fransina Hilli; Kurniayu Triastuti R.A. Ratu (Universitas Nusa Cendana, 2022)
The Use of Inquiry Learning Models on Various Style Materials to Improve Learning Outcomes of Fourth Grade Students at SD Negeri Oebole, Rote Ndao Regency. Data collection techniques are observation and tests. The data analysis technique is descriptive qualitative with 18 subjects, namely 6 men and 12 women. This study obtained results that showed that in the first cycle of 18 students there were 8 students who completed with a percentage of 44.44%, the acquisition score for student observations was 1,137.26 with an average value of 63.18 included in the sufficient category, while the average score was 63.18. the average for teacher observations is 69.11 in the sufficient category. Cycle II there were 18 students completed, the results of student observations obtained a score of 1,572.45 with a value of 87.35 in the very good category and the student test was 100% and the average value of teacher observations was 89.70 in the very good category. all students completed with a percentage score of 100% because students began to focus on paying attention to the learning material presented by the teacher, dared to answer questions given by the teacher and were active in group work according to the steps of the inquiry model.